2018
DOI: 10.3390/ma11112221
|View full text |Cite
|
Sign up to set email alerts
|

Indium-Zinc-Tin-Oxide Film Prepared by Reactive Magnetron Sputtering for Electrochromic Applications

Abstract: This paper reports on the fabrication of indium-zinc-tin-oxide (IZTO) transparent conductive film deposited by direct current (DC) reactive magnetron sputtering. The electrical, structural, and optical properties of IZTO film were investigated by Hall measurement, X-ray diffraction (XRD), and optical transmission spectroscopy with various sputtering powers. The IZTO film prepared used power at 100 W showed the lowest resistivity of 5.2 × 10−4 Ω cm. To accomplish rapid switching and high optical modulation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…We sought to elucidate the electrochemical properties of the WO 3 /ITO/glass and WO 3 /IZTO/PET by constructing three electrode cells, which comprised a working electrode (WO 3 film on TCO substrate), a counter-electrode (Pt mesh) and a reference electrode (Ag/AgCl) in a 0.2 M LiClO 4 /PC solution [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to elucidate the electrochemical properties of the WO 3 /ITO/glass and WO 3 /IZTO/PET by constructing three electrode cells, which comprised a working electrode (WO 3 film on TCO substrate), a counter-electrode (Pt mesh) and a reference electrode (Ag/AgCl) in a 0.2 M LiClO 4 /PC solution [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It presumes R 2 (the radius of Li x WO 3 particle for IZTO-based ECDs) is smaller than d (the distance of Li + ions and electrons can extract), which can explain electron and Li + ions can be extracted from the interior of Li x WO 3 for IZTO-based ECDs. However, R 1 (the radius of Li x WO 3 particle for ITO-based ECDs) is larger than d (the distance of Li + ions and electrons can extract), and this means electron and Li + ions cannot be extracted to the electrolyte from the Li x WO 3 particle completely, indicating the Li x WO 3 particles have some residual W 5+ ions in the process of fading oxidation that W 5+ cannot completely convert to W 6+ , leading to poor optical transmittance modulation [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knowing the membrane area resistance is important to assess the contribution of different functional groups [52]. Experimental studies reported in the literature showed that the resistance of IEMs is affected by the membrane structure, the relative sizes of the mobile phases, and the electrostatic interactions between the membrane charges and mobile cations [53,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the increase in the SiO 2 /Al 2 O 3 /ZnO nanoparticles allowing exchange and conduction of ions in the membrane. According to related research, the conductivity of an IEM is affected by three factors: the network structure within the membrane, the relative size of the IEC, and the composition of the exchange group [26,44,45]. The strength of the electrostatic coactions between the functional group fixed on the membrane and the cations reportedly relies on the membrane surface charge density and the cation valence [46].…”
Section: Resultsmentioning
confidence: 99%